Sulfur-centred polyoxoniobate-based 3D organic–inorganic hybrid compound and its magnetic behavior. Issue 72 (19th July 2016) - Hu, Ju-Fang; Han, Tian; Chi, Ying-Nan; Lin, Zheng-Guo; Xu, Yan-Qing; Yang, Song; Wei, Ding; Zheng, Yan-Zhen; Hu, Chang-Wen
Abstract : A novel sulfur-centered polyanion SNb8 V9.25 O45.25 was connected by cobalt-complexes into a 3D hybrid compound showing weak ferromagnetic interaction at low temperature. Abstract : The first sulfur-centered polyanion SNb8 V9.25 O45.25 was isolated, which is covalently extended by cobalt complexes into a three-dimensional (3D) architecture. Moreover, the resulting 3D organic–inorganic hybrid compound orders as a weak ferromagnet at low temperature.